Physical-mechanical behavior of alkali-activated materials produced by the one-part method based on fly ash and rice husk ash - Domingos,L. F. T. (2022)
Abstract The study on the physical-mechanical properties of alkali-activated materials (AAM) produced by the ‘one-part’ method was carried out. For this, residues such as fly ash and rice husk ash (RHA) were used. The alkaline activator (NaOH) was calcined together with RHA for 2 h at 750 °C. Dry mixes were prepared by replacing fly ash with 10%, 20%, and 30% by weight of the calcined material. The samples produced were characterized after 7 and 28 days of curing. The results showed that the investigated variables (calcined material content and curing time at room temperature) were responsible for important variations: compressive strength from 2.40 to 24.92 MPa, modulus of elasticity from 0.90 to 12.32 GPa, water absorption from 2.92% to 13.64%, apparent porosity from 4.82% to 20.02%, and density from 1.48 to 1.71 g/cm3. It was concluded that these variations were due to the high concentration of Na2O and SiO2 in the dry mixtures.